ID, EGO, ANDSUPEREGO REPRESENTED BY THE MAIN CHARACTEROFFIFTY SHADES OF GREYMOVIE CRHISTIAN GREY - Sudrazat, Riza Alun (LANTERN (Journal on English Language, Culture and Literature), 2017)
Fifty Shades of Grey is an American romantic drama movie directed by Sam Taylor-Johnson adapted from a novel by E.L James. The movie depicts the relationship between Christian Grey and Anastasia Steel. Omitted of this study analyzes the main character’s personality by discussing intrinsic and extrinsic aspects in this movie. The focus of this study is Christian Grey’s id, ego, and superego. To figure this out, the writer uses psychoanalysis approach by using Sigmund Freud’s theory on the id, ego, and superego. From this analysis, it can be concluded that Christian Grey’s personality is leaning on his id which is BDSM. BDSM denotes a set of erotic behaviors involving bondage and discipline, dominance and submission, sadism and masochism, and/or slave and master relationship. Then, his ego and superego works to restricts the id into nondestructive ways.